2021
DOI: 10.1002/ajs4.191
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility for homelessness: Lived experience perspectives and their alignment with neoliberal discourse

Abstract: In a context of increasing welfare conditionality, governmental responses to homelessness in Australia continue to be influenced by neoliberal discourses of personal responsibility. This is reflected in their emphasis on individualised interventions and lack of attention to structural drivers of homelessness. Research examining these issues has primarily focused on policies and practices aiming to responsibilise individuals' conduct, and less so on how those with lived experiences view and apportion responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Overall, findings revealed the Commonwealth and NSW State Government’s underlying belief that individuals can earn their access to financial and housing assistance through hard work suggesting the government’s underlying ideology of neoliberalism driven by a focus on privatisation which perpetuates the ‘ deserving and undeserving ’ narrative (Fenton, 2021; Stonehouse et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, findings revealed the Commonwealth and NSW State Government’s underlying belief that individuals can earn their access to financial and housing assistance through hard work suggesting the government’s underlying ideology of neoliberalism driven by a focus on privatisation which perpetuates the ‘ deserving and undeserving ’ narrative (Fenton, 2021; Stonehouse et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We opted for this methodological approach to emphasise the social and political dimensions of the problem of homelessness and the difficulties of access to health services for people experiencing homelessness. In terms of political dimensions, one can think of decreased funding in social programmes for access to employment and housing, budgetary restraint measures (neoliberal policies and austerity) and cuts in healthcare, among others (Donnan, 2014; Fazel et al, 2014; Gaetz et al, 2016; Stonehouse et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies have considered the (mis)alignment between existing approaches and lived experiences of homelessness. This has included the considerations of narratives and self-perceptions that question liberal individualized practices and advocate for more focus on structural constraints and systemic factors (Toolis and Hammack 2015;Stonehouse et al 2022). Research has shown the importance of governance in homelessness policy, pointing to the need for collaborative structures across levels of government, policy actors, and areas (see, for example, Doberstein 2016;Hafer 2018;Smith 2022).…”
Section: Le and Homelessnessmentioning
confidence: 99%